2009
DOI: 10.1016/j.childyouth.2009.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific mental health services for children in foster care

Abstract: Although a high proportion of foster children receive mental health services, existing research suggests limited accessibility and effectiveness of these services. This paper discusses strategies to develop a model to deliver evidence-based services using the unique opportunities apparent within publicly funded child welfare systems. An ecologically-focused model providing enhanced services in children's homes and schools could capitalize on these opportunities and radically improve access and effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…These factors affect the practices of both therapists who work in child welfare agencies and case managers who attempt to integrate mental health interventions into their home visits. In this context, providers might be particularly focused on their established roles and have difficulty incorporating more proactive mental health practices that are not viewed as essential to their central role (Leathers at al., 2009). Successful implementation may require distinct strategies that recognize how these distinct feature of the work environment affect intervention uptake and sustained use.…”
Section: Discussionmentioning
confidence: 99%
“…These factors affect the practices of both therapists who work in child welfare agencies and case managers who attempt to integrate mental health interventions into their home visits. In this context, providers might be particularly focused on their established roles and have difficulty incorporating more proactive mental health practices that are not viewed as essential to their central role (Leathers at al., 2009). Successful implementation may require distinct strategies that recognize how these distinct feature of the work environment affect intervention uptake and sustained use.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this perception, feasibility research that we conducted before initiating the intervention suggested that case managers believed that few of the foster parents served by the agency would voluntarily attend a group to receive the intervention (Leathers et al, 2009). To address this possibility, we developed a stand-alone home visiting protocol based on the manualized KEEP intervention which allowed us to provide the intervention to a greater proportion of foster parents.…”
Section: The Present Studymentioning
confidence: 82%
“…Child welfare systems are also subject to pressures related to high caseloads, high staff turnover, and a continual influx of new cases, creating stressed, difficult work climates that interfere with the sustained use of effective interventions (Glisson & Green, 2006). As case managers may be more concerned with “regulating” their cases than providing emotional support and information to clients, foster parents often feel unsupported and report experiencing greater parenting stress (Leathers et al, 2009), creating an additional barrier to effective treatment. Furthermore, mental health services for foster children are characterized by administrative barriers (Raghavan, Inkelas, Franke, & Halfon, 2007), low caregiver involvement (Zima et al, 2000; Orme & Buehler, 2001), and reliance on individual child treatment based on attachment theory with no empirical support (Barth et al, 2005).…”
Section: Development Of Mental Health Interventions For Foster Childrenmentioning
confidence: 99%
“…Other studies have explored evidence-based treatments and how they might be adapted to routine clinical practice (Hoagwood, Burns, Kiser, Ringeisen, & Schoenwald, 2001). Empirical literature suggests that an ecologically focused model providing enhanced home-based and school-based services substantially improved access to and effectiveness of mental health care (Leathers et al, 2009). This argues for shifting treatment from traditional mental health venues into more accessible locales.…”
Section: Appropriate Use Of Available Mental Health Servicesmentioning
confidence: 99%